2014
DOI: 10.1055/s-0034-1389950
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin Protects Against Spinal Cord Injury-induced Oxidative Stress and Inflammation in Wistar Rats through Nrf-2 Upregulation

Abstract: Taken together, the data suggests potential and novel role of Plumbagin in cytoprotection by modulating NF-κB and Nrf-2 levels against spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Oxidative stress‐induced inflammatory response is one of the major events in secondary injury; which ultimately leads to apoptosis with eventual loss of neurological function . Emerging evidence indicates that oxidative stress and inflammatory responses play critical role in SCI . Following SCI, the normally quiescent microglia are inevitably activated, with changes in morphology, proliferation, and release of cytokines and chemokines, finally becoming so‐called ‘reactive microglia’ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress‐induced inflammatory response is one of the major events in secondary injury; which ultimately leads to apoptosis with eventual loss of neurological function . Emerging evidence indicates that oxidative stress and inflammatory responses play critical role in SCI . Following SCI, the normally quiescent microglia are inevitably activated, with changes in morphology, proliferation, and release of cytokines and chemokines, finally becoming so‐called ‘reactive microglia’ .…”
Section: Discussionmentioning
confidence: 99%
“…22 Emerging evidence indicates that oxidative stress and inflammatory responses play critical role in SCI. 23,24 Following SCI, the normally quiescent microglia are inevitably activated, with changes in morphology, proliferation, and release of cytokines and chemokines, finally becoming so-called 'reactive microglia'. 25,26 As shown in this study, we found that proinflammatory MiRNAs are tiny endogenous RNAs that regulate gene expression at the post-transcriptional level and are capable of controlling specific cellular and physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effect of PL has been explained by its potential to activate Nrf2 (Chu et al, 2016; Son et al, 2010). Up-regulated Nrf2 protects the brain against blood-brain barrier breakdown (Alfieri et al, 2011), spinal cord injury (Zhang et al, 2015) and cerebral ischemia (Son et al, 2010). Therefore, Nrf2 may have a protective role in neurodegenerative diseases, including PD (Choi et al, 2012; Cuadrado et al, 2009), AD (Kanninen et al, 2008), and HD (Stack et al, 2010) as well as traumatic brain injury (Yan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations showed that PL inhibits NF-κB (Checker et al, 2009; Luo et al, 2010; T. Wang et al, 2014; Zhang et al, 2015) and the pro-inflammatory cytokines stimulated by NF-κB activation in the in vivo models of osteoporosis (Zheng et al, 2017). Furthermore, the protective effects of PL through inhibition of LPS-induced NO, cytokines and NF-κB release in mice and RAW 264.7 macrophage cells were reported (Checker et al, 2014; T.…”
Section: Introductionmentioning
confidence: 99%
“…Early relief of inflammation following SCI is involved in neural protection and the promotion of functional recovery. Nuclear factor (NF)-κB, tumor necrosis factor (TNF)-α and interleukin (IL)-1β have been reported to be significantly downregulated following plumbagin treatment in SCI rats (9). Nacar et al (10) revealed the beneficial effect of atorvastatin in rat SCI through anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%